Building the internet of things implement new business models, disrupt competitors, and transform your industry - Kranz, Maciej (Wiley, 2017)
Contents: Beyond the hype : all you actually need to know about IoT for business -- IoT is about change and transformation -- The promise of IoT is real -- Understanding the IoT business value proposition -- Four fast paths to an assured IoT payback -- Generation IoT goes to work -- Bringing IoT into your organization : change management -- Mistakes and how to avoid them -- IoT security essentials -- Standards and technology -- IoT state of the union.